The Interaction Between Protean Career Orientation, Career Goal Development and Well-being Outcomes: Evidence from Professional Engineers - Norizan Baba Rahim (Master in Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2020)
Experiencing strong personal development and growth are important for engineers, compared to professionals in other fields. Nevertheless, if career goal development behaviour is not present in sufficient quantities, engineers would be at risk if their own goals and expectations are not aligned with the companies they are working for. As a result, it may have a negative impact on their well-being. In this article, a sample of professional engineers (N=387) were utilised to examine the relationship between protean career orientation towards career goal development, career satisfaction and psychological well-being and to examine the mediating effect of career goal development between protean career orientation toward career satisfaction and psychological well-being. The research model was tested using the goal setting theory. The results of a partial least square (PLS) regression demonstrated that protean career orientation had a positive effect towards career goal development; subsequently career goal development had a positive effect on career satisfaction and psychological well-being. On the other hand, career goal development was found not to mediate the relationship between protean career orientation towards career satisfaction and psychological well-being. Based on the findings, this research suggests employers and industries encourage their unlicensed engineers to register as graduate engineers, so that later they can upgrade themselves to professional engineers’ status, as eventually this would help them to experience their job in a more meaningful way, and consequently increase their work happiness.